Dignified death in the Intensive Care Unit: How has it been conducted? - Ivankovics, Ivan Gregório; Vieira, Gislaine dos Santos Rodrigues; Faleiro, Lucas Freitas; Vieira, Thiago Felipe de Moraes; Romanini, Wdmila Gabriela Borges; Do Nascimento, Weylla Silva; Madueno Júnior, Carlos Rafael Hurtado; Júnior, Madueno; Nunes, Rui (Acta Bioethica, 2023)
The concept of dignified death or a good death has been widespread among health professionals, who routinely deal with it and experience the ethical dilemma about what should really be done in the face of a terminally ill patient. Given this, the present study aims to show the concepts and how cases of terminally ill patients have been conducted within the Intensive Care Units (ICU). To argue about the application and functionality of euthanasia, orthothanasia and dysthanasia in ICUs, a literature review of 14 articles was carried out. It was concluded that the knowledge that the professional has in relation to these themes needs to be taken into account and to distinguish the specific theme that is addressed, not forgetting to emphasize the rights provided for in the constitution and the well-being of the paciente and his family.